THE MITIGATING FACTORS OF GREENWASHING : A SYSTEMATIC LITERATURE REVIEW - Sari, Dica Yulinar; Windijarto, Windijarto (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2023)
Greenwashing is a strategy carried out by companies by presenting an image of good sustainable performance but hiding their actual environmental performance. Greenwashing harms investors and consumers. Therefore, this research will examine mitigation factors that can minimize the occurrence of greenwashing practices. This research method uses a Systematic Literature Review (SLR) with a database sourced from Scopus as many as 21 articles that are relevant to the topic of this study. It is hoped that the final results of this research will be useful in making policies related to greenwashing and as a basis for a development model for researchers related to greenwashing topics in the future.